Study on windbreak performance of tree canopy by numerical simulation method. (December 2018) - Jian, Zhang; Bo, Li; Mingyue, Wang
When airflow fly over trees, a shelter area will be generated at downstream area, and wind speed in the region will be reduced correspondingly. In order to analyze the windbreak performance of tree canopy, porous media method and additional source term are explored to simulate by computational fluid dynamics. Based on the given method, windbreak performance of trees with different canopy porosity, canopy shapes and distances between trees is investigated in detail, and characteristics of wind flow on the downstream of tree are shown. Results showed that small canopy porosity does not always mean good performance of windbreak, especially for the lower part. Canopy shapes only affect wind speed in the wake range. In these regions, windbreak performance of tree depends on the thickness of canopy. When distance is beyond 3H (H is the height of tree), wind speed becomes uniform at the downstream of tree and spacing can be equivalent to the porosity. But, for the region close to tree, trees with spacing cannot provide effective windshield. These simulations of tree canopy windbreak performance are conducted. All the results of the new model show better canopy flow characteristics through the field.